The influence of macroeconomic factors toward non-performing loans in Malaysia / Noor Farahanim Ariffin - Ariffin, Noor Farahanim (Faculty of Business and Management, 2018)
The purpose of this study was to investigate the influence of macroeconomic factors towards non-performing loans in Malaysia. The variables used to examine the relationship with non-performing loans (NPL) were interest rate (IR), inflation rate (INF), exchange rate (EXC) and unemployment rate (UR) from the year 2006 until 2016 on quarterly basis. The aim of this study was to find out the significant or insignificant of the variables towards the NPLs. As known, NPLs can be considered as an important issue in banking system as the results of NPLs will grant a huge impact not only to the banking system but also the Malaysian economy. This paper used Ordinary Least Square Methods in order to define the statistical relationship among variables. Next, this study proceeded with other tests which were Descriptive Analysis, Diagnostic Checking, Unit Root Tests and Multiple Regression. The result indicated that the exchange rate was the only insignificant variable toward NPLs. In addition, there were no diagnostic problems such as autocorrelation problem, heteroscedasticity problem and others.